Cerebrospinal fluid hemoglobin drives subarachnoid hemorrhage-related secondary brain injury. Issue 11 (November 2021) - Akeret, Kevin; Buzzi, Raphael M; Schaer, Christian A; Thomson, Bart R; Vallelian, Florence; Wang, Sophie; Willms, Jan; Sebök, Martina; Held, Ulrike; Deuel, Jeremy W; Humar, Rok; Regli, Luca; et al.
Secondary brain injury after aneurysmal subarachnoid hemorrhage (SAH-SBI) contributes to poor outcomes in patients after rupture of an intracranial aneurysm. The lack of diagnostic biomarkers and novel drug targets represent an unmet need. The aim of this study was to investigate the clinical and pathophysiological association between cerebrospinal fluid hemoglobin (CSF-Hb) and SAH-SBI. In a cohort of 47 patients, we collected daily CSF-samples within 14 days after aneurysm rupture. There was very strong evidence for a positive association between spectrophotometrically determined CSF-Hb and SAH-SBI. The accuracy of CSF-Hb to monitor for SAH-SBI markedly exceeded that of established methods (AUC: 0.89 [0.85-0.92]). Temporal proteome analysis revealed erythrolysis accompanied by an adaptive macrophage response as the two dominant biological processes in the CSF-space after aneurysm rupture. Ex-vivo experiments on the vasoconstrictive and oxidative potential of Hb revealed critical inflection points overlapping CSF-Hb thresholds in patients with SAH-SBI. Selective depletion and in-solution neutralization by haptoglobin or hemopexin efficiently attenuated the vasoconstrictive and lipid peroxidation activities of CSF-Hb. Collectively, the clinical association between high CSF-Hb levels and SAH-SBI, the underlying pathophysiological rationale, and the favorable effects of haptoglobin and hemopexin in ex-vivo experiments position CSF-Hb as a highly attractive biomarker and potential drug target.